Spatial control and symbolic politics at the intersection of China, India and Burma - Farrelly, N; Nicholas Samuel Farrelly (2011)
The Chinese, Indian and Myanmar governments share the borderlands in the corners of their respective territories where East, South and Southeast Asia meet. In this region of common concern the capacities of these three systems of post-colonial government are regulated so as to prevent excessive political conflict and discourage territorial fragmentation. My research focus is how the governments seek to exert spatial control in areas occupied by the closely-related Jingpo, Singpho and Jinghpaw peoples. As part of their efforts to shape interactions with the central governments, local elites among these peoples have defended and expanded elements of their Jingpo, Singpho and Jinghpaw cultures, particularly their annual Manau festivals. Seeking a way to analyse the relationship between governments and those they govern I draw on the illustrative potential of these large-scale events. It is the symbolic politics of these festivals that suggest an argument about spatial control that refines the state-repelling “Zomia” model proposed by van Schendel (2002) and Scott (2009a). I argue that nodes of control are sites where the governments concentrate power in order to manage their geopolitical ambitions. These nodes succeed when they encourage the acquiescence of local economic and cultural elites. By opening up opportunities for such collaboration, the nodes buttress the strategic links—cultural, political, economic, transportation and communications—that are the main interests of all central governments. It is, moreover, the intrinsic limitation of government ambitions, and their willingness to allow creative ambiguities, that suggests the direction in which ideas about spatial control at the intersection of China, India and Burma can be re conceived.